Diagnosis of real cracks from eddy current testing signals using parallel computation. Issue 4 (2nd October 2017) - Janousek, Ladislav; Rebican, Mihai; Smetana, Milan; Duca, Anton
Abstract: The paper presents a novel approach for three-dimensional diagnosis of partially conductive cracks from two-dimensional eddy current testing signals by means of the tabu search stochastic method. A new testing probe driving uniformly distributed eddy currents is employed for the inspection. Three spatial components of the perturbation electromagnetic field due to partially conductive cracks are sensed as the response signals in order to enhance information level of the inspection. The signals are simulated by a fast forward FEM-BEM solver using a database. Cracks are modeled as defects with a complex shape and homogeneous conductivity. The length, depth, width and conductivity of a detected crack are unknown in the inversion process. Numerical results of the three-dimensional reconstruction of partially conductive cracks from simulated two-dimensional signals are presented and discussed in the paper. Artificial white noise is added to the simulated signals and robustness of the algorithm is tested. Moreover, parallel computation is employed to reduce the computation time.